Design of Field Rental System on Web-Based Garuda Mataram Badminton Club - Khairan Marzuki; Anthony Anggrawan; Helna Wardhana; Lalau Ganda Rady Putra; Canggih Wahyu Rinaldi (JURNAL TEKNIK INFORMATIKA, 2023)
Residents of West Nusa Tenggara, Mataram City, mostly like badminton. GOR Badminton Garuda is a sports building that provides sports field rental services specifically for badminton (badminton) in the city of Mataram. Rental management at the Garuda Badminton Building is still carried out conventionally, namely by manually recording the list of field tenants in the rental book, resulting in difficult data searches and frequent schedule recording errors. In addition, making reports takes a long time because they are still made from rental books. In terms of field reservation, it is also considered less effective because tenants have to come to the field. The solution provided is to create a web-based online field rental information system using the Waterfall method. The results of creating this information system can make it easier for admins to manage rentals and make it easier for the public to get information and field booking services online. Based on Usability testing using the ISO 9126 model, the Field Rental Information System at the Garuda Badminton Sports Hall is in good criteria with a percentage of 83%.